Preparation method of self-repairing negative carbon cement-based grouting material based on gradient structure

Through self-healing of negative-carb cement-based grouting materials with gradient structure, the cracks of cement-based grouting materials are repaired using calcium bicarbonate and calcium alginate hydrogels, which solves the shrinkage and de-emphasis problems of cement-based grouting materials, and improves the The reinforcement effect and density ensure the long-term survival and repair effect of microorganisms.

CN119306447AActive Publication Date: 2025-01-14ZAOZHUANG MINING GRP ZHONGXING JIANAN ENG CO LTD

Patent Information

Application Number
CN202411647424.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-14
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The cement-based grouting material has inevitable shrinkage deformation during the hardening process, resulting in shrinkage cracks and the phenomenon of de-emphasis between the grouting material and the repaired structure, limiting the performance of the reinforcement effect.

Method used

Using the preparation method of self-healing negative-carb cement-based grouting material based on gradient structure, the excess carbon dioxide in the calcium carbide slag soaking liquid is converted into calcium bicarbonate, and combined with silicate cement-based grouting material and microbial sodium alginate repair material , form a composite grouting material, and the microbial-sodium alginate repair material is distributed in a gradient manner in the cement-based grouting material through degassing and sonication, forming a calcium alginate hydrogel to repair cracks.

Benefits of technology

It effectively solves the problem of de-emphasis between the grouting material and the repaired structure, improves the reinforcement effect, enhances the density and bonding strength of the grouting material, ensures the long-term survival and repair effect of microorganisms, and significantly improves the injection. The effect of slurry reinforcement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306447A_ABST
    Figure CN119306447A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, which comprises the following steps: (1) adding carbide slag into water for fully soaking, then separating out a soaking solution, then introducing excessive carbon dioxide into the soaking solution to convert calcium hydroxide into calcium bicarbonate, and obtaining a mixing solution after completion; and (2) uniformly mixing the mixing liquid, a Portland cement-based grouting material and a microorganism-sodium alginate repair material to obtain the composite grouting material. (3) degassing the composite grouting material, and then carrying out ultrasonic treatment, so that one part of the microorganism-sodium alginate repairing material is diffused to the outer layer of the cement-based grouting material, and the other part of the microorganism-sodium alginate repairing material is embedded into the cement-based grouting material; thus, the characteristic that the concentration of the microorganism-sodium alginate repairing material in the cement-based grouting material is gradually increased from inside to outside and is in gradient distribution is formed, and the self-repairing negative carbon cement-based grouting material is obtained. The grouting material not only can repair shrinkage cracks, but also can fully fill a grouting material void area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grouting materials, and in particular to a preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the acceleration of underground engineering construction, the demand for the construction and maintenance of underground infrastructure has increased significantly. The application of grouting materials in civil engineering for repairing and reinforcing structures has become increasingly important, and they are widely used in many fields such as construction, mining, and water conservancy. Grouting materials are mainly divided into cement-based grouting materials, polymer-based grouting materials, resin-based grouting materials, etc. Since cement-based grouting materials are mainly made of a mixture of cement, sand and water, they have the advantages of convenient raw material acquisition, excellent durability, simple process, and high cost performance. They are suitable for projects with high bearing requirements and are currently widely used in reinforcement projects. However, cement-based grouting materials inevitably shrink and deform during the hardening process, which leads to shrinkage cracks. At the same time, shrinkage will also cause the grouting material matrix and the repaired structure to appear empty. These factors greatly limit the grouting reinforcement effect of cement-based grouting materials.

[0004] In response to the above problems, engineers currently generally use organic grouting materials such as polyurethane or organic latex powder for secondary grouting to control the voiding phenomenon between the grouting material and the repaired structure. However, this method not only complicates the construction process and increases the project cost, but also the organic grouting material has poor durability and is limited in application. Summary of the invention

[0005] In view of the above problems, the present invention provides a preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, which can not only repair shrinkage cracks, but also fill the grouting material empty area to improve the reinforcement effect. Specifically, the technical solution of the present invention is as follows.

[0006] A preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, comprising the following steps: (1) Add carbide slag into water and soak it thoroughly, then separate the soaking liquid, and then introduce excess carbon dioxide into it to convert calcium hydroxide into calcium bicarbonate. After completion, a mixing liquid is obtained.

[0007] (2) The mixing liquid, silicate cement-based grouting material and microorganism-sodium alginate repair material are mixed to obtain a composite grouting material.

[0008] (3) The composite grouting material is subjected to a degassing treatment and then an ultrasonic treatment, so that a portion of the microorganism-sodium alginate repair material diffuses into the outer layer of the cement-based grouting material, while the other portion is embedded in the cement-based grouting material, thereby forming a gradient distribution characteristic in which the concentration of the microorganism-sodium alginate repair material in the cement-based grouting material gradually increases from the inside to the outside, that is, a self-repairing negative carbon cement-based grouting material is obtained.

[0009] Furthermore, in step (1), the mass ratio of the carbide slag to water is 1:8-20.

[0010] Furthermore, in step (1), the soaking time is 1 to 2 hours.

[0011] Furthermore, in step (1), the rate of introducing carbon dioxide is 10-15 L / min. After the introduction of carbon dioxide, the soaking liquid first becomes turbid, and then becomes clear again as the carbon dioxide continues to be introduced, thereby obtaining the mixing liquid.

[0012] Furthermore, in step (2), the mass ratio of the mixing liquid, silicate cement-based grouting material, and microorganism-sodium alginate repair material is 0.2~0.5:1.0:0.005~0.02.

[0013] Furthermore, in step (2), the silicate cement-based grouting material includes silicate cement, silica fume and organic latex powder. Optionally, the ratio of silicate cement, silica fume and organic latex powder is 60-70 parts by weight: 7-12 parts by weight: 2-3 parts by weight.

[0014] Furthermore, in step (2), the microorganism-sodium alginate repair material is prepared by the following method: adding Bacillus pasteurianus microbial liquid to water and mixing, and then adding sodium alginate, urea and calcium acetate, and mixing to obtain the repair material.

[0015] Furthermore, the ratio of the Bacillus pasteurianus microbial liquid, water, sodium alginate, urea and calcium acetate is 10-17 mL: 100-110 ml: 0.7-1.5 g: 4-8 g: 12-20 g. Optionally, the number of live bacteria in the Bacillus pasteurianus microbial liquid is 1×10 12 ~1×10 14 CFU.

[0016] Furthermore, in step (3), the degassing treatment method is vibration degassing. Optionally, the vibration frequency is 3-5 Hz, and the vibration time is 10-30 min.

[0017] Furthermore, in step (3), the ultrasonic treatment time is 10-30 min, and the power is 200-400 W.

[0018] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: The self-repairing negative carbon cement-based grouting material of the present invention effectively solves the problem that the traditional cement-based grouting material is not dense, has gaps, shrinks itself, and causes gaps between the grouting material and the crack surface of the repaired structure, resulting in poor grouting reinforcement effect. The reason is: (1) The present invention first uses excess carbon dioxide to modify the leachate of carbide slag, which can not only consume carbon dioxide, offset part of the carbon emissions generated in the production of cement in the silicate cement-based grouting material, and reduce the carbon footprint of the cement-based grouting material. In addition, the calcium bicarbonate contained in the obtained mixing liquid reacts with the calcium hydroxide produced by cement hydration in the hardening stage after grouting the grouting material to form calcium carbonate, which fills the grouting material matrix and improves the density. At the same time, by consuming the calcium hydroxide produced by the hydration, the alkalinity of the grouting material is reduced, which is more conducive to the survival of microorganisms in the microbial-sodium alginate repair material, so that it can better play the role of repairing cracks in the grouting material matrix.

[0019] (2) The present invention utilizes ultrasonic treatment to diffuse a portion of the microorganism-sodium alginate repair material into the outer layer of the cement-based grouting material, while the other portion is embedded in the cement-based grouting material, thereby forming a characteristic that the concentration of the microorganism-sodium alginate repair material in the cement-based grouting material gradually increases from the inside to the outside and presents a gradient distribution. After the grouting material is injected into the cracks, the sodium alginate reacts with the calcium ions released by the hydration of cement to form a calcium alginate hydrogel, which absorbs moisture in the environment and expands, thereby fixing the microorganisms in the cracks and secreting calcium carbonate to repair the cracks. Due to the above-mentioned concentration gradient distribution characteristics, most of the hydrogel and calcium carbonate are enriched between the grouting material and the crack surface, thereby not only increasing the bonding strength between the grouting material and the crack surface, but also effectively solving the problem of cavitation between the grouting material and the crack surface caused by shrinkage of the grouting material and incomplete grouting, thereby greatly improving the grouting reinforcement effect. At the same time, when cracks are generated in the grouting material, the calcium alginate hydrogel can quickly repair itself, thereby improving the grouting reinforcement effect.

[0020] (3) The present invention utilizes the density difference between the silicate cement-based grouting material and the microorganism-sodium alginate repair material to make the repair material present an asymmetric concentration distribution characteristic in the grouting material, which significantly improves the utilization efficiency of the repair material and avoids the problem that the grouting material is easily ineffective in the cement-based material due to the alkaline environment for a long time. Under the anchoring effect of calcium alginate hydrogel, Bacillus pasteurianus microorganisms can use nutrients such as urea to secrete calcium carbonate to seal the cracks for a long time, avoiding the problem of microbial loss caused by traditional methods such as brushing or soaking. At the same time, Bacillus pasteurianus microorganisms are protected by calcium alginate hydrogel and do not directly contact the alkaline environment of cement, which is conducive to their long-term survival. The present invention distributes most of the microorganism-sodium alginate repair material on the periphery of the grouting material, effectively avoiding the alkaline environment of cement. In addition, the effect of calcium bicarbonate in the above-mentioned mixing liquid on reducing the alkalinity of the grouting material can effectively improve the living conditions of microorganisms. It not only ensures the long-term effectiveness of microorganisms, but also is consistent with the cracking law of the grouting material. The cracks gradually develop from the outside to the inside, so that the crack repair can take effect at the very beginning, reducing the problem of reduced reinforcement effect of the grouting material caused by cracks. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] It should be noted that the drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention and do not constitute an improper limitation of the present invention.

[0022] Figure 1 A sample diagram of a self-repairing negative carbon cement-based grouting material based on a gradient structure prepared in the following Example 1; Figure 2 The scanning electron microscope image of the self-repairing negative carbon cement-based grouting material based on the gradient structure prepared in the following Example 1; Figure 3 The following is a strength recovery performance test diagram of Example 1. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The preferred implementation methods and materials described in the present invention are only for demonstration purposes. The reagents or raw materials used in the invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or are used according to the product specification. Now the technical scheme of the present invention is further described in conjunction with specific embodiments.

[0024] Example 1 A preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, comprising the following steps: (1) Mix carbide slag and water in a mass ratio of 1:10, stir evenly, and then let it stand for 2 hours. After completion, filter out the soaking liquid, then place the soaking liquid in a transparent container, and continuously introduce carbon dioxide into the soaking liquid through the gas pipe at a rate of 12L / min. The exhausted carbon dioxide gas is collected and reused. When the soaking liquid first becomes turbid, and then becomes clear again as carbon dioxide continues to be introduced, the mixing liquid is obtained and is ready for use.

[0025] (2) Mix 42.5 ordinary Portland cement, silica fume and latex powder VAE in a ratio of 63 parts by weight: 8 parts by weight: 2.5 parts by weight and stir evenly to obtain a Portland cement-based grouting material for later use.

[0026] (3) Weigh the following raw materials in the following proportions: DSM 33 Bacillus pasteurianus microbial solution (number of viable bacteria: 1.7×10 13 CFU), water, sodium alginate, urea and calcium acetate = 15mL: 100ml: 1g: 5g: 15g. Then add the Bacillus pasteurianus microbial liquid to the water and stir evenly, then add the sodium alginate first, stir evenly, then add the urea and calcium acetate, stir evenly to obtain the microorganism-sodium alginate repair material, and set aside.

[0027] (4) The mixing liquid of this embodiment, the silicate cement-based grouting material and the microorganism-sodium alginate repair material are mixed in a mass ratio of 0.35:1.0:0.015 and stirred evenly to obtain a composite grouting material for use.

[0028] (5) The composite grouting material was placed in a container and vibrated on a vibration platform with a frequency of 5 Hz for 20 minutes to remove the gas in the slurry. The container was then sealed with a sealing cover and placed in water in an ultrasonic cleaning machine and treated with an ultrasonic power of 400 W for 15 minutes to obtain a self-repairing negative carbon cement-based grouting material. The sample Figure 1 shown.

[0029] Figure 2 This is a scanning electron microscope image of the interior of the self-repairing negative carbon cement-based grouting material of this embodiment after hardening. It can be seen that the surface of the grouting material is covered with a layer of hair-like gel, which evenly expands outward. These gels can effectively block the empty areas of the grouting material, and can also repair cracks, thereby improving the reinforcement effect of the grouting material.

[0030] Performance test: The pressure corresponding to 80% of the load of the 28d compressive strength of the concrete sample is set as the load damage pressure value. Then the above-mentioned pressure load is applied to the concrete sample and maintained for 30 seconds to obtain a pressure load damaged cracked concrete sample. The grouting material prepared in this embodiment is injected into the cracks of the cracked concrete sample until it is full, and it is placed under standard curing conditions for 7 days. At the same time, a cracked concrete sample that has not been repaired by grouting is set as a control group, and then the compressive strength of the above-mentioned specimens is tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019). The results are as follows Figure 3 As shown. It can be seen that when cracked and without any treatment, the compressive strength of the concrete sample is only 12.07MPa. After being repaired with the grouting material prepared in this embodiment, the strength of the concrete sample (repaired group) is 25.11MPa, which is 13.05MPa higher than that of the control group, and the strength recovery rate reaches 108.12%, showing a good grouting reinforcement effect.

[0031] Example 2 A preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, comprising the following steps: (1) Mix carbide slag and water in a mass ratio of 1:8 and stir evenly, then let it stand for 1.5 hours. After completion, filter out the soaking liquid, then place the soaking liquid in a transparent container, and continuously introduce carbon dioxide into the soaking liquid through the gas pipe at a rate of 10L / min. The exhausted carbon dioxide gas is collected and reused. When the soaking liquid first becomes turbid and then becomes clear again as carbon dioxide continues to be introduced, the mixing liquid is obtained and is ready for use.

[0032] (2) Mix 42.5 ordinary Portland cement, silica fume and latex powder VAE in a ratio of 70 parts by weight: 12 parts by weight: 3 parts by weight and stir evenly to obtain a Portland cement-based grouting material for later use.

[0033] (3) Weigh the raw materials according to the following proportions: DSM 33 Bacillus pasteurianus microbial solution (the number of viable bacteria is 1×10 14 CFU), water, sodium alginate, urea and calcium acetate = 10mL: 105ml: 0.7g: 4g: 12g. Then add the Bacillus pasteurianus microbial liquid to the water and stir evenly, then add the sodium alginate first, stir evenly, then add the urea and calcium acetate, stir evenly to obtain the microorganism-sodium alginate repair material, and set aside.

[0034] (4) The mixing liquid of this embodiment, the silicate cement-based grouting material and the microorganism-sodium alginate repair material are mixed in a mass ratio of 0.5:1.0:0.02 and stirred evenly to obtain a composite grouting material for use.

[0035] (5) After the composite grouting material is placed in a container, it is placed on a vibration platform with a frequency of 3 Hz and vibrated for 30 minutes to remove the gas in the slurry. Then, the container is sealed with a sealing cover and placed in water in an ultrasonic cleaner and treated with an ultrasonic power of 200 W for 30 minutes to obtain a self-repairing negative carbon cement-based grouting material.

[0036] The strength recovery rate of the grouting material prepared in this embodiment for cracked concrete specimens was tested using the same method as in the above-mentioned embodiment 1, and the result was 113.76%, showing a good grouting reinforcement effect.

[0037] Example 3 A preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, comprising the following steps: (1) Mix carbide slag and water in a mass ratio of 1:20, stir evenly, and then let it stand for 1 hour. After completion, filter out the soaking liquid, then place the soaking liquid in a transparent container, and continuously introduce carbon dioxide into the soaking liquid through the gas pipe at a rate of 15L / min. The exhausted carbon dioxide gas is collected and reused. When the soaking liquid first becomes turbid and then becomes clear again as carbon dioxide continues to be introduced, the mixing liquid is obtained and is ready for use.

[0038] (2) Mix 42.5 ordinary Portland cement, silica fume and latex powder VAE in a ratio of 60 parts by weight: 7 parts by weight: 2 parts by weight and stir evenly to obtain a Portland cement-based grouting material for later use.

[0039] (3) Weigh the raw materials according to the following proportions: DSM 33 Bacillus pasteurianus microbial solution (the number of viable bacteria is 1×10 12 CFU), water, sodium alginate, urea and calcium acetate = 17mL: 110ml: 1.5g: 8g: 20g. Then add the Bacillus pasteurianus microbial liquid to the water and stir evenly, then add the sodium alginate first, stir evenly, then add the urea and calcium acetate, stir evenly to obtain the microorganism-sodium alginate repair material, and set aside.

[0040] (4) The mixing liquid of this embodiment, the silicate cement-based grouting material and the microorganism-sodium alginate repair material are mixed in a mass ratio of 0.2:1.0:0.005 and stirred evenly to obtain a composite grouting material for use.

[0041] (5) After the composite grouting material is placed in a container, it is placed on a vibration platform with a frequency of 5 Hz and vibrated for 10 minutes to remove the gas in the slurry. Then, the container is sealed with a sealing cover and placed in water in an ultrasonic cleaning machine and treated with an ultrasonic power of 300 W for 10 minutes to obtain a self-repairing negative carbon cement-based grouting material.

[0042] The strength recovery rate of the grouting material prepared in this embodiment for cracked concrete specimens was tested using the same method as in the above-mentioned embodiment 1, and the result was 119.43%, showing a good grouting reinforcement effect.

[0043] Example 4 A preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, comprising the following steps: (1) Mix carbide slag and water in a mass ratio of 1:10, stir evenly, and then let it stand for 2 hours. After completion, filter out the soaking liquid, then place the soaking liquid in a transparent container, and continuously introduce carbon dioxide into the soaking liquid through the gas pipe at a rate of 12L / min. The exhausted carbon dioxide gas is collected and reused. When the soaking liquid first becomes turbid, and then becomes clear again as carbon dioxide continues to be introduced, the mixing liquid is obtained and is ready for use.

[0044] (2) Mix 42.5 ordinary Portland cement, silica fume and latex powder VAE in a ratio of 63 parts by weight: 8 parts by weight: 2.5 parts by weight and stir evenly to obtain a Portland cement-based grouting material for later use.

[0045] (3) Weigh the following raw materials in the following proportions: DSM 33 Bacillus pasteurianus microbial solution (number of viable bacteria: 1.7×10 13 CFU), water, sodium alginate, urea and calcium acetate = 15mL: 100ml: 1g: 5g: 15g. Then add the Bacillus pasteurianus microbial liquid to the water and stir evenly, then add the sodium alginate first, stir evenly, then add the urea and calcium acetate, stir evenly to obtain the microorganism-sodium alginate repair material, and set aside.

[0046] (4) The mixing liquid of this embodiment, the silicate cement-based grouting material and the microorganism-sodium alginate repair material are mixed in a mass ratio of 0.35:1.0:0.015 and stirred evenly to obtain a composite grouting material for use.

[0047] (5) The composite grouting material is placed in a container and vibrated on a vibration platform with a frequency of 5 Hz for 20 minutes to remove the gas in the slurry, thereby obtaining a self-repairing negative carbon cement-based grouting material.

[0048] The strength recovery rate of the grouting material prepared in this embodiment for cracked concrete samples was tested using the same method as in the above-mentioned embodiment 1, and the result was 86.27%.

[0049] Example 5 A preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, comprising the following steps: (1) Weigh the following raw materials in the following proportions: DSM 33 Bacillus pasteurianus microbial solution (the number of viable bacteria is 1×10 12 CFU), water, urea and calcium acetate = 17mL: 110ml: 8g: 20g. Then add the Bacillus pasteurianus microbial liquid into the water and stir evenly, then add the urea and calcium acetate, stir evenly to obtain the microbial repair material, and set aside.

[0050] (2) Mix the mixing liquid (the same as in Example 3 above), the silicate cement-based grouting material, and the microbial remediation material of this example in a mass ratio of 0.2:1.0:0.005 and stir evenly to obtain a composite grouting material for later use.

[0051] (3) After the composite grouting material is placed in a container, it is placed on a vibration platform with a frequency of 5 Hz and vibrated for 10 minutes to remove the gas in the slurry. Then, the container is sealed with a sealing cover and placed in water in an ultrasonic cleaner and treated with an ultrasonic power of 300 W for 10 minutes to obtain a self-repairing negative carbon cement-based grouting material.

[0052] The strength recovery rate of the grouting material prepared in this embodiment for cracked concrete specimens was tested using the same method as in the above-mentioned embodiment 1, and the result was 98.31%.

[0053] Example 6 A preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, comprising the following steps: (1) Mix 42.5 ordinary Portland cement, silica fume and latex powder VAE in a ratio of 70 parts by weight: 12 parts by weight: 3 parts by weight and stir evenly to obtain a Portland cement-based grouting material for later use.

[0054] (2) Clean water, silicate cement-based grouting material and microorganism-sodium alginate repair material (the same as in Example 2) are mixed in a mass ratio of 0.5:1.0:0.02 and stirred evenly to obtain a composite grouting material for later use.

[0055] (3) After the composite grouting material is placed in a container, it is placed on a vibration platform with a frequency of 3 Hz and vibrated for 30 minutes to remove the gas in the slurry. Then, the container is sealed with a sealing cover and placed in water in an ultrasonic cleaner and treated with an ultrasonic power of 200 W for 30 minutes to obtain a self-repairing negative carbon cement-based grouting material.

[0056] The strength recovery rate of the grouting material prepared in this embodiment for cracked concrete samples was tested using the same method as in the above-mentioned embodiment 1, and the result was 94.05%.

[0057] Example 7 A preparation method of a self-repairing negative carbon cement-based grouting material based on a gradient structure, comprising the following steps: (1) Mix carbide slag and water in a mass ratio of 1:10 and stir evenly, then let it stand for 2 hours. After completion, filter out the soaking liquid, and then place the soaking liquid in a transparent container to obtain the mixing liquid for later use.

[0058] (2) Mix 42.5 ordinary Portland cement, silica fume and latex powder VAE in a ratio of 63 parts by weight: 8 parts by weight: 2.5 parts by weight and stir evenly to obtain a Portland cement-based grouting material for later use.

[0059] (3) Weigh the following raw materials in the following proportions: DSM 33 Bacillus pasteurianus microbial solution (number of viable bacteria: 1.7×10 13 CFU), water, sodium alginate, urea and calcium acetate = 15mL: 100ml: 1g: 5g: 15g. Then add the Bacillus pasteurianus microbial liquid to the water and stir evenly, then add the sodium alginate first, stir evenly, then add the urea and calcium acetate, stir evenly to obtain the microorganism-sodium alginate repair material, and set aside.

[0060] (4) The mixing liquid of this embodiment, the silicate cement-based grouting material and the microorganism-sodium alginate repair material are mixed in a mass ratio of 0.35:1.0:0.015 and stirred evenly to obtain a composite grouting material for use.

[0061] (5) After the composite grouting material is placed in a container, it is placed on a vibration platform with a frequency of 5 Hz and vibrated for 20 minutes to remove the gas in the slurry. Then, the container is sealed with a sealing cover and placed in water in an ultrasonic cleaner and treated with an ultrasonic power of 400 W for 15 minutes to obtain a self-repairing negative carbon cement-based grouting material.

[0062] The strength recovery rate of the grouting material prepared in this embodiment for cracked concrete samples was tested using the same method as in the above-mentioned embodiment 1, and the result was 83.64%.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a self-repairing negative carbon cement-based grouting material based on a gradient structure, characterized in that: The steps include: (1) adding carbide slag into water to fully soak it, separating the soaking liquid, and then introducing excess carbon dioxide into the soaking liquid to convert calcium hydroxide into calcium bicarbonate, and obtaining a mixing liquid after completion; (2) mixing the mixing liquid, silicate cement-based grouting material and microorganism-sodium alginate repair material to obtain a composite grouting material; (3) The composite grouting material is subjected to a degassing treatment and then an ultrasonic treatment, so that a portion of the microorganism-sodium alginate repair material diffuses into the outer layer of the cement-based grouting material, while the other portion is embedded in the cement-based grouting material, thereby forming a gradient distribution characteristic in which the concentration of the microorganism-sodium alginate repair material in the cement-based grouting material gradually increases from the inside to the outside, that is, a self-repairing negative carbon cement-based grouting material is obtained.

2. The method for preparing the gradient structure-based self-repairing negative carbon cement-based grouting material according to claim 1, characterized in that: In step (1), the mass ratio of the carbide slag to water is 1:8-20.

3. The method for preparing the self-repairing negative carbon cement-based grouting material based on the gradient structure according to claim 1, characterized in that: In step (1), the soaking time is 1 to 2 hours.

4. The method for preparing the self-repairing negative carbon cement-based grouting material based on the gradient structure according to claim 1, characterized in that: In step (1), the rate of introducing carbon dioxide is 10-15 L / min; after the introduction of carbon dioxide, the soaking liquid first becomes turbid, and then becomes clear again as the carbon dioxide continues to be introduced, thereby obtaining the mixing liquid.

5. The method for preparing the gradient structure-based self-repairing negative carbon cement-based grouting material according to claim 1, characterized in that: In step (2), the mass ratio of the mixing liquid, silicate cement-based grouting material, and microorganism-sodium alginate repair material is 0.2~0.5:1.0:0.005~0.

02.

6. The method for preparing the gradient structure-based self-repairing negative carbon cement-based grouting material according to claim 1, characterized in that: In step (2), the silicate cement-based grouting material includes silicate cement, silica fume and organic latex powder; optionally, the ratio of silicate cement, silica fume and organic latex powder is 60-70 parts by weight: 7-12 parts by weight: 2-3 parts by weight.

7. The method for preparing the self-repairing negative carbon cement-based grouting material based on a gradient structure according to claim 1, characterized in that: In step (2), the microorganism-sodium alginate repair material is prepared by the following method: adding Bacillus pasteurianus microbial liquid to water and mixing, and then adding sodium alginate, urea and calcium acetate, and mixing to obtain the repair material.

8. The method for preparing the gradient structure-based self-repairing negative carbon cement-based grouting material according to claim 7, characterized in that: The ratio of the Bacillus pasteurianus microbial liquid, water, sodium alginate, urea and calcium acetate is 10-17 mL: 100 ml: 0.7-1.5 g: 4-8 g: 12-20 g; Optionally, the number of live bacteria in the Bacillus pasteurianus microbial liquid is 1×10 12 ~1×10 14 CFU.

9. The method for preparing the self-repairing negative carbon cement-based grouting material based on a gradient structure according to any one of claims 1 to 8, characterized in that: In step (3), the degassing method is vibration degassing; optionally, the vibration frequency is 3-5 Hz, and the vibration time is 10-30 min.

10. The method for preparing the gradient structure-based self-repairing negative carbon cement-based grouting material according to any one of claims 1 to 8, characterized in that: In step (3), the ultrasonic treatment time is 10-30 min, and the power is 200-400 W.

Citation Information

Patent Citations

  • Device and method for preparing particle-reinforced gradient composite materials by using ultrasonic waves

    CN101775518A

  • Concrete crack repairing material with sodium alginate immobilized microorganisms and preparation method of concrete crack repairing material

    CN114213153A

Cited By

  • Preparation process of concrete material with carbon reduction and microcrack self-repairing functions

    CN121698618A

  • A preparation process of a concrete material with carbon reduction and micro-crack self-repairing functions

    CN121698618B